2011
DOI: 10.1016/j.worlddev.2011.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dietary Quality: Evidence from Bangladesh

Abstract: Whereas a large number of empirical studies have been devoted to analyzing consumer demand for dietary energy (or dietary quantity), much less attention has been paid to the demand for dietary quality, an equally important aspect of food security. To address this gap in the literature, this paper uses data from a nationally representative household expenditure survey conducted in Bangladesh in 2000 on the food acquisition behavior of 7,440 households over a two week period. Two indicators of dietary quality ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
79
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 23 publications
17
79
1
5
Order By: Relevance
“…This finding is consistent with a study conducted in Bangladesh [21] where land ownership was reported to positively influence women dietary diversity. Vitamin A rich fruits 13 5 Organ meat 10 4 Fish and sea food 4 2 Adjusted for socioeconomic and demographic characteristics (education level, marital status, occupation, household head, level of income, source of lighting, livestock ownership and household assets) and morbidity incidence Findings of this study are in agreement with findings of several other studies which have reported that dietary diversity is associated with socioeconomic status [19,[22][23][24][25]. For instance, a study by Vakili et al [25] in Ahvaz-Iran showed a significant relationship between DDS and the economic situation of the respective respondents (p < 0.05).…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with a study conducted in Bangladesh [21] where land ownership was reported to positively influence women dietary diversity. Vitamin A rich fruits 13 5 Organ meat 10 4 Fish and sea food 4 2 Adjusted for socioeconomic and demographic characteristics (education level, marital status, occupation, household head, level of income, source of lighting, livestock ownership and household assets) and morbidity incidence Findings of this study are in agreement with findings of several other studies which have reported that dietary diversity is associated with socioeconomic status [19,[22][23][24][25]. For instance, a study by Vakili et al [25] in Ahvaz-Iran showed a significant relationship between DDS and the economic situation of the respective respondents (p < 0.05).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, similar to Rashid et al (2011) we made use of zero-truncated Poisson regression model to estimate Eq. 21 when DDS is used as the dependent variable.…”
Section: Determinants Of Household Demand For Dietary Diversitymentioning
confidence: 99%
“…Thus, the predicted fitted value of the instrumented-total expenditure is then used in the final analysis reported in Tables 3 and 4 as HHINCOME. As noted by Rashid et al (2011), this type of approach is becoming increasingly popular in the absence of detailed information on household income. The results of the multinomial model showing the effects of household's socioeconomic and demographic characteristics on the probability of households being food insecure, are presented in Table 3.…”
Section: Determinants Of Households In Different Levels Of Food Securitymentioning
confidence: 99%
“…Following standard practice in the literature on nutrition, the theoretical starting point for our investigation is household utility (e.g., Behrman et al 1997;Pitt and Rosenzweig 1985;Rashid et al 2011). We base our analysis on the agricultural household model taking market imperfections -mainly incomplete food markets due to remoteness -into account.…”
Section: Estimation Strategymentioning
confidence: 99%